The Role of Glutamate Signaling in Pain Processes and its Regulation by GCP II Inhibition - M. Wozniak, K.; Rojas, C.; Wu, Y.; S. Slusher, B. (Current Medicinal Chemistry, 2012)
Glutamate is the predominant excitatory neurotransmitter used by primary afferent synapses and neurons in the spinal cord dorsal horn. Glutamate and glutamate receptors are also located in areas of the brain, spinal cord and periphery that are involved in pain sensation and transmission. Not surprisingly, glutamate receptors have been an attractive target for new pain therapies. However, their widespread distribution and array of function has often resulted in drugs targeting these sites having undesirable side-effects. This chapter will review, in general terms, the current knowledge of glutamate and its effects at various glutamate receptors with regards to nociception. In addition, we will briefly review the glutamatergic drugs currently in use as treatments for pain, as well as known novel candidates in various stages of clinical trial. Lastly, we will summarize the data supporting a novel target for pain intervention by way of GCPII inhibition, which appears devoid of the side-effects associated with direct glutamate receptor antagonists and thus holds major promise for future therapy. GCPII (glutamate carboxypeptidase II) cleaves the prevalent neuropeptide NAAG into NAA and glutamate and there is widespread evidence and belief that targeting the glutamate derived from this enzymatic action may be a promising therapeutic route.
Keywords: pain